2017
DOI: 10.1017/jns.2017.20
|View full text |Cite
|
Sign up to set email alerts
|

The impact of time of neutering on weight gain and energy intake in female kittens

Abstract: Neutering is a risk factor for obesity in companion animals. In a study to determine the total energy requirements of kittens (15–52 weeks) the impact of neutering and age when neutered on intake and body weight (BW) was investigated. Females (n 14), neutered when 19 (early neuter; EN) or 31 (conventional neuter; CN) weeks old (n 7/group), were individually fed to maintain an ideal body condition score (BCS). EN kittens gained weight gradually whilst CN kittens’ BW gain slowed from week 24, weighing less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 19 publications
(23 reference statements)
0
14
0
2
Order By: Relevance
“…Previous editorials have signposted to resources and evidence 13 45. This includes evidence around a lack of osteoporotic risks due to delayed physeal closure,51 weight gain,49 52 urinary tract problems29 34 or behaviour problems30 31 49 for cats neutered prepubertally compared with a traditional age. Additionally, evidence suggests neutering prior to 6 months greatly reduces the risk of mammary tumours 53.…”
Section: Discussionmentioning
confidence: 99%
“…Previous editorials have signposted to resources and evidence 13 45. This includes evidence around a lack of osteoporotic risks due to delayed physeal closure,51 weight gain,49 52 urinary tract problems29 34 or behaviour problems30 31 49 for cats neutered prepubertally compared with a traditional age. Additionally, evidence suggests neutering prior to 6 months greatly reduces the risk of mammary tumours 53.…”
Section: Discussionmentioning
confidence: 99%
“…Two equations are proposed (1) to estimate energy requirements of cats: one for non-obese and another for obese animals. However, several other factors besides body composition may interfere with the energy expenditure (EE) of felines (2) . Male cats, for example, tend to be heavier, with more lean and less fatty mass than females, and may present higher EE (3)(4)(5) .…”
mentioning
confidence: 99%
“…Gonadectomy has been shown to reduce the metabolic rate of cats, thus increasing the risk of obesity. However, long‐term studies have not found a correlation between the age at neutering and subsequent susceptibility to obesity (Spain and others 2004, Allaway and others 2017). It is not possible to ascertain the exact effect of neutering on obesity due to the multitude of factors which may influence an animal's propensity to become obese (ie, diet, exercise and genetics).…”
Section: Risks and Disadvantages Of Neuteringmentioning
confidence: 99%